PENGARUH MODEL PEMBELAJARAN READ, ANSWER, DISCUSS, EXPLAIN, AND CREATE (RADEC) TERHADAP KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA KELAS XI IPS MA AS`ADIYAH ULOE KABUPATEN BONE - Indarwati. S; Aisyah Nuryam; A.M. Irfan Taufan Asfar (De Fermat : Jurnal Pendidikan Matematika, 2023)
The low ability to think creatively in Indonesia encourages educational institutions to develop effective learning models. The purpose of this research is to: (1) See the influence of Read, Answer, Discuss, Explain, and Create (RADEC) learning on students' creative mathematical thinking abilities (2) To find out how students respond to the Read, Answer, Discuss, Explain, and learning model. Create (RADEC) on the mathematical creative thinking abilities of class XI IPS MA As`adiyah Uloe students in Bone Regency. The research method used is quantitative research with the Quasi Experimental Design type. The research population included all students of class XI MA As'adiyah Uloe, Bone Regency, totaling 45 students consisting of 2 classes, namely class The sampling technique uses saturated sampling. Research data was collected through written tests (pretest and posttest) and student response questionnaires. The results of the research show that there is an influence of the Read, Answer, Discuss, Explain, and Create (RADEC) learning model on the Mathematical Creative Thinking Ability of Class Very Good Category)